Urgent attention from BUCG to help expedite progress for the lift and escalator work of BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding urgent attention from BUCG to help expedite progress for the lift and escalator work of BRAC University new campus project.